PREPARATION OF MICRO, SMALL, MEDIUM ENTERPRISES FINANCIAL STATEMENTS FOR THAI COMMUNITY USING THE MICROSOFT EXCEL APPLICATION (International Journal of Innovative Technologies in Economy, 2022)
Micro, Small, and Medium Enterprises (MSMEs) have an important role to develop the economy of ASEAN Countries, particularly in Thailand. To monitor the development of MSMEs, the stakeholders need information about business activities of the MSMEs. The Financial Statement able to give information of business performance in each period of the development of MSMEs. Then, the role of information technology, especially software to support the implementation of financial statement to the enterprises. But, a few of entrepreneur understand how to operate software, particularly Microsoft Excel in making financial statement to the MSMEs. So, the role of scholars from higher education are important to teach the entrepreneur of MSMEs in making financial statements through microsoft excel application. This article aims to describe how the lecturers of business faculty of Universitas Kristen Maranatha, Bandung, Indonesia to train the entrepreneurs of MSMEs in Thailand in making financial statement through Microsoft Excel application. The result of our community service are the entrepreneurs of MSMEs in Thailand understand how to make financial statements using Microsoft Excel application.